Physical and chemical interfacial engineering of Mg anodes for rechargeable magnesium batteries - Hyungjin Lee; Jangwook Pyun; Inkyoung Han; Haewon Kim; Seunghyeop Baek; Yeonu Lee; Jihun Roh; Doron Aurbach; Seung-Tae Hong; Munseok S. Chae (Journal of Magnesium and Alloys)
Rechargeable magnesium batteries are promising alternatives to traditional lithium batteries because of the high abundance of Mg compounds in earth crust, their low toxicity, and possible favorable properties as electrodes’ material. However, Mg metal anodes face several challenges, notably the natively existence of an inactive oxide layer on their surfaces, which reduces their effectiveness. Additionally, interactions of Mg electrodes with electrolyte solutions’ components can lead to the formation of insulating surface layers, that can fully block them for ions transport. This review addresses these issues by focusing on surface treatments strategies to enhance electrochemical performance of Mg anodes. It highlights chemical and physical modification techniques to prevent oxidation and inactive-layers formation, as well as their practical implications for MIBs. We also examined the impact of Mg anodes’ surface engineering on their electrochemical reversibility and cycling efficiency. Finally, future research directions to improve the performance and commercial viability of magnesium anodes and advance development of high-capacity, safe, and cost-effective energy storage systems based on magnesium electrochemistry are discussed.